Myocyte proliferation in the developing heart - Sedmera, David; Thompson, Robert P (Developmental dynamics, 2011)
Regulation of organ growth is critical during embryogenesis. At the cellular level, mechanisms controlling the size of individual embryonic organs include cell proliferation, differentiation, migration, and attrition through cell death. All these mechanisms play a role in cardiac morphogenesis, but experimental studies have shown that the major determinant of cardiac size during prenatal development is myocyte proliferation. As this proliferative capacity becomes severely restricted after birth, the number of cell divisions that occur during embryogenesis limits the growth potential of the postnatal heart. We summarize here current knowledge concerning regional control of myocyte proliferation as related to cardiac morphogenesis and dysmorphogenesis. There are significant spatial and temporal differences in rates of cell division, peaking during the preseptation period and then gradually decreasing toward birth. Analysis of regional rates of proliferation helps to explain the mechanics of ventricular septation, chamber morphogenesis, and the development of the cardiac conduction system. Proliferation rates are influenced by hemodynamic loading, and transduced by autocrine and paracrine signaling by means of growth factors. Understanding the biological response of the developing heart to such factors and physical forces will further our progress in engineering artificial myocardial tissues for heart repair and designing optimal treatment strategies for congenital heart disease.
Keywords: Cell Differentiation; vývojová regulace genové exprese; Cell Proliferation; Morphogenesis; Myocytes, Cardiac; Gene Expression Regulation, Developmental; Models, Biological; myokard; zvířata; Humans; Myocardium; biologické modely; Heart; proliferace buněk; morfogeneze; kardiomyocyty; buněčná diferenciace; srdce; lidé; Animals